Criminal Law Analysis of the Exploitation of Women in the Film Sang Penari - I Putu Edi Rusmana (Journal Equity of Law and Governance, 2024)
This study examines these issues within the framework of Indonesia's criminal law development, focusing on the film Sang Penari. Through the character Srintil, the film vividly portrays how cultural practices can entrap women in cycles of exploitation that are legitimized by societal expectations. Although Indonesia has adopted various progressive legal regulations such as Law No. 21/2007 on the Eradication of Trafficking in Persons and Law No. 23/2004 on the Elimination of Domestic Violence, implementation in the field still faces significant challenges. Lack of effective law enforcement, lack of public awareness, and socio-economic factors, such as poverty, contribute to the vulnerable situation for women. Therefore, to protect women from exploitation and violence, a multidimensional approach is needed that includes aspects of law, education and economic empowerment. This research emphasizes the need for integration between law, culture and social awareness so that women like Srintil can live with dignity and be protected from violence and exploitation.